Molecular detection of mecA gene in methicillin-resistant Staphylococcus aureus isolated from dairy mastitis in Nineveh governorate, Iraq - Shit, Umar Hashim (Iraqi journal of veterinary sciences, 2022)
تعتبر المكورات العنقودية الذهبية هي العامل المسبب الرئيسي لالتهاب الضرع البقري في جميع أنحاء العالم. بالإضافة إلى ذلك، فان المكورات العنقودية الذهبية المقاومة للميثيسيلين هي بكتيريا ممرضة رئيسية في مجال الطب البيطري و الصحة العامة. تم جمع ستة و ستين عينة من حليب الأبقار بشكل عشوائي من مناطق مختلفة من محافظة نينوى خلال الفترة من تشرين الثاني 2018 إلى شباط 2020. في هذه الدراسة، تم استخدام طرق البيولوجي الجزيئية و الكلاسيكية لتحديد جراثيم المكورات العنقودية الذهبية المقاومة للميثيسيلين و اكتشاف الجينات المستهدفة. أوضحت نتائج الدراسة الحالية أن جراثيم المكورات العنقودية الذهبية تم عزلها و تحديدها على أساس الطرق التقليدية مثل الكاتلاز و عوامل التكتل و اختبار تجلط الدم. بالإضافة إلى ذلك، تم الكشف عن جين nuc في جميع عزلات المكورات العنقودية الذهبية الإيجابية 23 (34.8٪)، بينما تم الكشف عن جي mecA في 12 عزلة (52.2٪) من جراثيم المكورات العنقودية الذهبية المقاومة للميثيسيلين باستخدام تقنية تفاعل البلمرة المتسلسل. أظهرت الدراسة الحالية أن نتائج الطرق التقليدية و تقنية تفاعل البلمرة المتسلسل كانت متشابهة. تعتبر جراثيم المكورات العنقودية الذهبية المقاومة للميثيسيلين في العراق عاملا مسببا رئيسيا لأنواع مختلفة من التهاب الضرع في الأبقار و لها القدرة على مقاومة جميع أنواع مجموعة بيتا لاكتام. تم عزل جراثيم المكورات العنقودية الذهبية المقاومة للميثيسيلين من مناطق في مدينة الموصل. تعد تقنية تفاعل البلمرة المتسلسل طريقة رئيسية للكشف عن الجينات المختلفة بناء على التسلسل المستهدف للجين المحد. Staphylococcus (S.) aureus is universally the leading aetiologic cause of dairy mastitis. Additionally, methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogenic bacterium in veterinary medicine and public health. Sixty-six cattleʼs milk samples were collected randomly from different areas of the Nineveh Province from November 2018 to February 2020. In this study, the classical and molecular biology methods had used to identify the MRSA and detect the target genes. The results revealed that S. aureus was isolated and identified based on classical methods such as catalase, clumping factors, and coagulase test. In addition, the nuc gene was detected in all the positive S. aureus isolates 23 (34.8%), while the mecA gene was detected in 12 (52.2%) MRSA isolates by using polymerase chain reaction (PCR) assay. The present work emerged that the results of classical methods and the PCR technique were similar. MRSA is regarded as a significant causative agent of various types of bovine mastitis in Iraq, and it can to resist all types of beta-lactams. MRSA isolated from different regions in Mosul city. PCR assay is a powerful method for detecting the different genes based on the target sequence of the specific gene.